The effect of project-based learning model on PGSD students’ critical thinking skill - Nada Savitri Nawangsari; Pratiwi Pujiastuti; Dhiniaty Gularso (Jurnal Prima Edukasia, 2022)
This study aims to determine the effect of the project-based learning learning model on the thinking skills of PGSD students in the Social Sciences 1 course. The method used in this research is an experiment. The subjects in this study were PGSD students. There are two classes in this research design, namely the experimental class and the control class. The experimental class consisted of 37 students and the control class also consisted of 37 students. Data collection techniques used observation and document analysis. The data analysis technique used in this research is descriptive analysis calculated by comparing the average value of each variable with the standard curve criteria. The analysis prerequisite test uses the normality test. The hypothesis test used is the t-test. The results showed that the project-based learning model has a significant effect in improving students' critical thinking skills.